Modulation of Atlantic Multidecadal Oscillation on the Interdecadal Variation of South Asian High and Somali Jet in Summer - Shi, Wenjing; Wang, Qingzhe; Xiao, Ziniu; Cheng, Wei; Duan, Wei (Frontiers in Earth Science, 2021)
As two important components of the Asian summer monsoon system, the intensities of South Asian High (SAH) and Somali jet (SMJ) in summer exhibit both interannual and decadal variabilities. On the interdecadal time scale, the temporal evolution of the SAH intensity is in phase with that of the SMJ intensity. By comparison, we find that both of them evolve synchronously with the Atlantic Multidecadal Oscillation (AMO), with AMO cold/warm phases corresponding to the weakening/ strengthening of SAH and SMJ. Further diagnoses indicate that the interdecadal variability of the SAH and SMJ intensity in summer may be modulated by AMO phase. Mechanistically, this modulation appears to be achieved via an interdecadal Silk Road pattern (SRP)–like wave train along the Asian westerly jet and Matsuno–Gill tropical atmospheric response. The cold SST anomaly over extratropical North Atlantic related to AMO– firstly induces an anomalous high over Western Europe and produces a well–organized wave train between 30oN and 60oN. The anomalous Iranian Plateau low along with the wave train path leads to a weakened SAH. Besides, the AMO– related cold SST anomalies over tropical North Atlantic cool the tropical tropospheric atmosphere through the moist adjustment process and produce a Matsuno–Gill–like atmospheric response covering the tropical Indian Ocean. Due to the Matsuno–Gill response, subsidence motion anomalies over the central tropical Indian Ocean corresponding to a result in increased lower–level divergence and upper–level convergence are excited over tropical Indian Ocean. Finally, the tropical Indian Ocean divergence in lower troposphere leads to the weakened summer SMJ, and the tropical Indian Ocean convergence in upper troposphere results to the reducing and northward displacement of SAH in summer.